THE Peran Stres Kerja dalam Memediasi Gaya Kepemimpinan Kolaboratif terhadap Kinerja Pegawai di Kantor Pelayanan Pajak Pratama Jambi - Muhammad Nopbrima; Zulfina Adriani; Syahmardi Yacob (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
This research was conducted at KPP Pratama Jambi to determine the role of work stress in mediating collaborative leadership styles on employee performance. The research conducted was qualitative research, with a total of 112 respondents, and was processed using the partial least square (PLS) application. The testing process is carried out in four stages, namely outer model, inner model, and hypothesis testing. The tests that have been carried out have yielded results, namely there is a positive and significant influence between collaborative leadership style on work stress with a significant value of 0.000, between leadership style on employee performance with a significant result of 0.001, between work stress on employee performance with a significant value of 0.045, and between work stress mediating collaborative leadership style on employee performance with a significant result of 0.047 and all hypotheses Accepted. The conclusion found is that collaborative leadership styles can help employees manage work stress so that employee performance is maximized.